Effect of sintering procedures on optical properties, chemical composition, and grain size of monolithic zirconia ceramic at different thicknesses after hydrothermal aging: An in vitro study - Haydar Albayrak; Ravza Eraslan; Ömer Aydinlioglu (Wolters Kluwer Medknow Publications, 2023)
Aim: The purpose of the present study was to examine the optical properties, chemical composition, and grain size (GS) of monolithic zirconia (MZ) ceramic at different thicknesses sintered using different procedures after hydrothermal aging. Settings and Design: An in vitro study. Materials and Methods: Forty MZ discs (0.5-mm thickness [Group-0.5] and 1-mm thickness [Group-1]; 12 mm diameter) were milled and divided according to standard (Group-ST) and speed (Group-SP) sintering procedures. All specimens were hydrothermally aged at 134°C after sintering. Translucency (TP), opalescence (OP), and fluorescence (ΔEabFNx01-FL) parameters were calculated using the color coordinates (LFNx01, aFNx01, bFNx01, respectively) of the discs. The chemical composition and the GS of the specimens were characterized using X-ray fluorescence spectroscopy and a scanning electron microscopy, respectively. Statistical Analysis Used: TPs and ΔEabFNx01-FLs were analyzed using independent samples t-tests and Mann-Whitney U-tests while a two-way analysis of variance (ANOVA) was used for OPs. Results: Group-1 showed significantly lower TP than Group-0.5 (P < 0.001) but a significantly higher OP (P = 0.014). Group-SP showed significantly higher OP (P = 0.00003) and ΔEabFNx01-FL (P = 0.0026) values than Group-ST without considering the thickness. Group-SP (0.29 ± 0.119 μm) had a smaller GS than Group-ST (0.306 ± 0.142 μm). Compared to Group-ST, Group-SP had a lower percentage of Y2O3 and a higher percentage of Al2O3. Conclusion: The effect of the sintering procedure on TP and OP of MZ was not perceived by the naked eye. The speed sintering procedure may increase Δ EFNx01ab-FL of MZ to higher values than natural teeth when compared with standard sintering. The speed sintering may cause minor changes in GS and the chemical composition of MZ.